Transforming traditional Kerinci carving motifs into creative products: a qualitative study of cultural transmission and heritage sustainability - Nofrial Nofrial; Yuliarni Yuliarni; Ferawati Ferawati; Widdiyanti Widdiyanti (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2026)
This study analyzes the transformation of traditional Kerinci carving motifs into creative products as an entry point for cultural heritage revitalization within a heritage based creative economy framework. It examines motif transformation as a multi level process linking changes in cultural knowledge, design adaptation, and cultural ecosystem revitalization. Using a qualitative case study approach, data were collected through semi-structured interviews, observation, visual documentation, and literature review in Kerinci Regency and Sungai Penuh City, involving 25 purposively and snowball-selected informants. Data were analyzed through open coding, constant comparison, and thematic interpretation based on heritage revitalization, cultural sustainability, and the heritage-based creative economy. Results indicate that transformation is driven not only by design innovation but also by weakening intergenerational knowledge transmission, shifting motifs from cultural meaning systems into fragmented visual resources. Motif adaptation remains non-standardized and highly dependent on individual initiatives. The study proposes a five-stage revitalization model linking documentation, design transformation, product innovation, artisan regeneration, and pentahelix ecosystem strengthening for cultural sustainability.